2020
DOI: 10.1088/1361-6595/ab5e46
|View full text |Cite
|
Sign up to set email alerts
|

Electron density, temperature and the potential structure of spokes in HiPIMS

Abstract: In high power impulse magnetron sputtering (HiPIMS) bright plasma spots are observed during the discharge pulses that rotate with velocities in the order of 10 km s−1 in front of the target surface. It has proven very difficult to perform any quantitative measurements on these so-called spokes, which emerge stochastically during the build-up of each plasma pulse. In this paper, we propose a new time shift averaging method to perform measurements integrating over many discharge pulses, but without phase averagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(62 citation statements)
references
References 57 publications
(93 reference statements)
4
55
1
Order By: Relevance
“…The resemblance between the time-evolution of n e (t) and I D (t) during the HiPIMS pulse has been observed before experimentally by Held et al [27]. It can be understood by equalizing the discharge current with the ion current to the target.…”
Section: Influence Of the Magnetic Field And The Discharge Current On...supporting
confidence: 54%
“…The resemblance between the time-evolution of n e (t) and I D (t) during the HiPIMS pulse has been observed before experimentally by Held et al [27]. It can be understood by equalizing the discharge current with the ion current to the target.…”
Section: Influence Of the Magnetic Field And The Discharge Current On...supporting
confidence: 54%
“…The measurements reveal the existence of a double layer structure with large electric field at the leading edge of the ionization zone and that this double layer plays a crucial role in the energization of electrons [103]. References [101], [102] discuss the experimentally determined potential structures of spokes in HIPIMS. The presence of a double layer and enhanced ionization at the spoke front is reminiscent of the Critical Ionization Velocity model of [105] and of the PIC simulations of [63], [106], although the velocity of the spoke measured in HiPIMS and magnetron discharges does not necessarily match the theoretical critical ionization velocity.…”
Section: State Of the Art And Recent Progressmentioning
confidence: 94%
“…As mentioned above, the dense HiPIMS plasma near the target is not homogeneous, and can exhibit one or more spokes with a rotational velocity of about 10 km s −1 in the E ⃗ ⃗ × B ⃗ ⃗ azimuthal direction. Recently, Held et al [38] characterized the plasma potential inside those structures using time-shift averaging Langmuir probe measurements. They reported that the plasma potential becomes higher inside a spoke than in the surrounding region, with the measured potential in those structures being positive and having a weak gradient.…”
Section: Iii31 Population 3 (15-50 Ev)mentioning
confidence: 99%